The Social World of the Babylonian Priest - Still, Bastian, (Culture and History of the Ancient Near East, 2019)
In The Social World of the Babylonian Priest , Bastian Still presents a comprehensive study of the priestly community of Borsippa during the Neo-Babylonian and early Persian Empires (ca. 620-484 BCE). By examining patterns of marriage, landholding, moneylending, and friendship, he provides an intimate account of the daily life of the Babylonian priesthood beyond the temple walls and develops a more sophisticated understanding of the organisation of ancient Babylonian society as a whole. Combining the use of social network analysis, anthropological studies, and sociological concepts concerned with kinship, tie strength, social boundaries, and identity formation, Bastian Still's interdisciplinary approach transcends the traditional boundary of cuneiform studies and enables the field of Assyriology to contribute to a more general socio-historical discourse.